Using Sweep Frequency Response Analysis and Dissolved Gas Analysis in Diagnosing of Power Transformer: Published online: 06/03/2026 - Nguyen, Hoang Minh Vu (Journal of Technical Education Science, 2026)
This article presents two diagnostic techniques for assessing the mechanical and electrical condition of oil-immersed power transformers: sweep frequency response analysis (SFRA) and dissolved gas analysis (DGA). The SFRA method detects potential mechanical faults in transformer windings by applying the correlation coefficient (Rxy). For a 63 MVA, 115/23/11 kV transformer, experimental results show that the winding is considered normal when RLF ≥ 2.0, RMF ≥ 1.0, and RHF ≥ 0.6, whereas RLF < 0.6 indicates severe deformation. In contrast, the DGA method identifies internal faults such as partial discharge, low-energy and high-energy discharges, and thermal faults by analyzing gas concentrations in the insulating oil. For a 20 MVA, 110/22 kV transformer, measured gas concentrations (µl/l, ppm) include H₂ (0.00), CH₄ (40.43), C₂H₆ (18.24), C₂H₄ (20.92), C₂H₂ (0.00), CO₂ (8932.66), and CO (2131.18), corresponding to a “thermal fault below 300°C.” Both diagnostic methods are integrated into user-friendly MATLAB-based tools to support testing centers in Vietnam. The combination of SFRA and DGA enhances diagnostic accuracy, enables timely maintenance decisions, and contributes to improving the reliability of power supply systems.